Soluciones barriales participativas, caso de estudio, barrio El Carmen parroquia Malacatos, cantón y provincia de Loja, periodo 2023-2024. - Cuenca Mendieta, Mayeli Wendy (2024)
This research focuses on the use of citizen participation as a means of optimising administration, management and public administration in the El Carmen neighbourhood, Malacatos Parish, Loja Province. It was proposed to contribute to society in the construction of effective solutions through the application of mechanisms of citizen participation in accordance with the reality of the El Carmen neighbourhood, so the specific objectives were focused on collaborating with the neighbourhood organisation in the diagnosis of its main problems, providing training on the mechanisms of citizen participation to empower neighbourhood leadership and collaborating in the generation of spaces for the inhabitants of the neighbourhood to participate before the local institutional authorities, aimed at mitigating the demands of the citizens. A mixed methodology was used, where qualitative information was collected through direct observation and interviews, while the quantitative aspect was carried out through surveys of residents and neighbourhood leadership. The results revealed critical problems such as the deterioration of the infrastructure and the lack of basic services, as well as the need to legalise the ownership of the community house. Citizen participation training was carried out to empower neighbourhood leadership, promoting participation in community management. Efforts to generate spaces for dialogue between residents and local authorities resulted in agreements and commitments to activities focused on needs and priorities to improve the community house. This participatory process demonstrated the effectiveness of community inclusion in decision-making and local sustainable development. The conclusions emphasised the importance of citizen participation in governance and community collaboration for sustainable development and improved quality of life in the El Carmen neighbourhood.